2019
DOI: 10.1002/anie.201905670
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesis of Odd‐Numbered Tetraaryl[n]cumulenes

Abstract: A mechanochemical synthesis of one‐dimensional carbon allotrope carbyne model compounds, namely tetraaryl[n]cumulenes (n=3, 5) was realized. Central for the mechanosynthesis of the cumulenic carbon nanostructures were the development of a mechanochemical Favorskii alkynylation‐type reaction and the implementation of a solvent‐free, acid‐free reductive elimination with tin(II) chloride by ball milling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…However, in most cases the reduction in derivatization steps in mechanochemical C−H functionalization reactions is an intrinsic advantage of the general concept of direct C−H activation, rather than the result of the implementation of the mechanochemical approach. This is different from examples such as the previously discussed mechanosynthesis of propargylic diols 4 and 1,4‐diamino‐2‐butynes 9 in which the need for acetylene derivatives (e. g., metal acetylides) [48–50] was avoided by implementing mechanochemistry (Scheme 3).…”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 67%
See 2 more Smart Citations
“…However, in most cases the reduction in derivatization steps in mechanochemical C−H functionalization reactions is an intrinsic advantage of the general concept of direct C−H activation, rather than the result of the implementation of the mechanochemical approach. This is different from examples such as the previously discussed mechanosynthesis of propargylic diols 4 and 1,4‐diamino‐2‐butynes 9 in which the need for acetylene derivatives (e. g., metal acetylides) [48–50] was avoided by implementing mechanochemistry (Scheme 3).…”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 67%
“…In the search for better alternatives, scientists have identified solid CaC 2 as a safer surrogate of acetylene, which not only have exhibited a wide versatility in synthetic chemistry, [46] but which also displays an interesting circular sustainability profile. [47] By mechanochemistry, CaC 2 has enabled the solventfree preparation of cumulenes 6 by: (i) shortening the synthetic route, (ii) avoiding the use of Li-or Mg-acetylide in the synthesis of propargylic alcohols 4, [48,49] and (iii) accomplishing the stannous chloride mediated reductive elimination of 4 without the need for corrosive Brønsted acids such as hydrochloric acid (Scheme 3a). [48] Moreover, the application of CaC 2 as a C 2 synthon has enabled the one-pot mechanosynthesis of 1,4-diamino-2-butynes 9 by copper catalysis.…”
Section: Gc 3: Less Hazardous Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Such reactions avoid bulk solvents and heat, offering a greener alternative to solution methods . However, mechanochemistry can also be a tool for reaction discovery and development, enabling the synthesis of previously inaccessible molecules, and offering transformations and selectivities that are not seen in solution . We previously reported that mechanochemistry enabled copper‐catalyzed C−N coupling of sulfonamides or sulfonimides with isocyanates or carbodiimides, providing rapid access to sulfonylureas, sulfonylguanidines and benzoazepines .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Uniquely, mechanochemistry also offers opportunities to prepare chemical compounds that are otherwise difficult or impossible to prepare by solution methods owing to limited solubility of the starting material and the limited stability of the product in solution. 3,4 In recent years, mechanochemistry has increasingly been applied as a benign synthetic route in a wide range of fields. [5][6][7][8][9][10][11] (e.g., organometallic complexes, [12][13][14] organo-catalysts, 15 cocrystals [16][17][18] , metal-organic frameworks, [19][20][21] alloys, 22 composites, 23 etc.…”
Section: Introductionmentioning
confidence: 99%